INTRODUCTION OF TRUSTED COMPUTING PLATFORM IN CLOUDCOMPUTING - Aayushi Bamboli; Nilofar Tamboli; Pallavi Ghadage; Manisha Mohite (International Journal of Innovations in Engineering Research and Technology, 2021)
We knew that cloud computing is could be usage of computer resources accessible via internet. Author has tried designing business model, which uses for divide and rule mechanism. Advantage of developed techniques is, by dividing the responsibility among different cloud services benefit to the clients. The implemented business model uses three sub models for encryption and decryption services, storage devices with CRM services. Both encryption and decryption data depends on cloud computing , the system administrator may simultaneously obtain both encrypted data and decryption keys to provide security authentication of user is done, invalid user is not allow to use the data.